(untitled) - Stuart Corbridge (New York, 1993)
The book explores the workingsof the world economy in three main ways. The introductory section sets the modern world economy in its historical context, paying particular attention to the economic effects of European expansionism and imperialism after 1492. The main body of the book goes on to examine the workings of the contemporary world economy in 22 of its constituent regions. A third way is to explore the human dimensions of apparently abstract economic actions, theories and ideologies
Keywords: economic history - encyclopedias